Phytoremediation of herbicide quizalofop-ethyl contaminated soil by Sesbania sesban L. for public health - Mahakavi,, Thangavelu G; Baskaran, Logalakshmanam G (International Multidisciplinary Research Journal, 2016)
In world food production, agricultural pollution is a major concern. Nowadays in agriculture farmers using different toxic herbicide, pesticide, and other harmful chemical products were used control, the weeds, and pest. So, the presence of this kinds of toxic chemical harmfully affect the Funa and also while consuming the food the chemical reach to the human beings and it will create the cancer also, so that it must be control for public health in that way the present work deals how to remove the chemicals by plants through field experiment. In this field experiment, sandy loam soil was treated with a different level of herbicide (quaizalofop-ethyl) 0.5, 1.0, 1.5 and 2.0%, and Sesbania sesban L. seeds were sown in all treatment soil. The morphological parameters were measured after 20, 40, and 80 days. The results indicate that all the morphological parameters were increased in control then it was gradually decreased with increasing the herbicide concentration. Hence, after 80 days plants were harvested and the harvested plant powder was analyzed for absorption of herbicide by the plant with the help of gas chromatography mass spectrum. The obtained data showed that herbicide absorption was concerned in quaizalofop-ethyl treated plant when compared to control. This study reveals that residues of herbicide were reduced by S. sesban L.